The effects of salinity on changes in characteristics of soils collected in a saline region of the Mekong Delta, Vietnam - Van Tan Lam (De Gruyter, 2021)
Due to the impacts of climate change and the reduction in the flow of the Mekong River, saline intrusion into the inland has been an emergent and pressing issue. The purpose of this study is to analyze the effects of various saline conditions (0–25‰) on changes in some soil properties under laboratory conditions. Ten topsoil samples were collected from a depth of 0–20 cm in the dry seasons in the rice–corn rotation fields with low salinity, in Thanh Phu district, Ben Tre province, Vietnam. The examined criteria consisted of soil pH, soil electrical conductivity of the saturated paste extract (ECe), exchangeable Na, percentage of exchangeable Na, and content (%) of nitrogen and phosphorus. The results revealed that the pH range of soil decreased from 5.14–5.72 to 4.08–5.14 when the soil salinity increased from 0 to 25‰. At the salinity of 10‰ and higher, the available nitrogen began to decline. Meanwhile, the available phosphorus tended to decrease as the salinity increased past 12‰. Some measures are also discussed, with the aim of ensuring sustainable rice farming in the circumstances of increased salinity.